Hans Tausen: Kampen for en dansk Luther - Dreyer, Rasmus H.C. (Dansk Teologisk Tidsskrift, 2011)
The article is a historiographical examination of the reception of the Danish reformer Hans Tausen: The Lutheran Orthodox theologians (late 16th-17th century) distanced themselves from Tausen, as they identified his theology as ‘Zwinglian’. Pietism and Rationalism (second half of the 18th century), in contrast, defended Tausen and even called him the ‘Danish Luther’ because of what they saw as ‘Lutheran’ aspects of his theology. A critical focus (from around 1850) did not change the general description. The article emphasizes that the examinations of the 20th century are still to be grouped into two, since the focus either is on the ‘Lutheran’ perspectives or Tausen as influenced by the ‘humanistic’ Reformation, by some alternatively identified as a kind of ‘Philippistic’ or ‘Wittenberg’ theology. A renewed examination of Tausen’s theology must rather be understood as a synthesis of continuity and reorientation.